Utilidad del volumen medio plaquetario como predictor de severidad y mortalidad en pacientes sépticos - Vélez Páez, Jorge Luis (2021)
Background. Sepsis is a public health problem with high prevalence and mortality. Biomarkers are a tool to determine diagnosis, severity and prognosis in these patients. Platelet mean volume (MPV), a biomarker reported in routine blood counts, has been investigated and shows promise for determining strong outcomes in septic patients Objective. To assess whether the VMP is an independent predictor of severity and mortality in patients with sepsis. In addition, verify the behavior of the VMP / platelets ratio for the same outcome variables. Materials and methods. Prospective study of secondary data that included 163 adult patients admitted to the intensive care unit, diagnosed with sepsis under SEPSIS criteria. 3; in which the MPV in fentoliters (fL) and the MPV / platelet ratio were measured on days 1, 2 and 3. Mortality at 28 days and clinical severity (estimated as SOFA score and presence of septic shock). Bivariate analyzes were performed to compare the clinical characteristics and laboratory parameters between non-survivors and survivors. Chi square was applied for categorical variables and the Mann-Whitney test was used for quantitative variables. Survival analysis was performed comparing the curves using the Log Rank test (Mantel-Cox), and the Cox regression as a multivariate analysis. Results. It was found that in patients with sepsis, elevated values of MPV on day 3 and of the MPV / platelet ratio on days 2 and 3 were associated with mortality; and with cut-off points in MPV of> 9.45fL (day 1) and> 9.15fL (day 3) and a ratio of> 6.04,> 5.53 and> 3.95 on all follow-up days, determined mortality in the survival curves and were independent predictors of mortality when analyzed individually with the regression of COX with HR for VMP day 1 of 2.09 (95% CI 1.19-3.70 p: 0.011), VMP day 3 of 2.37 (CI95% 1.13-4.97 p: 0.023) and for the ratio VMP / platelets day 1 1.82 (CI95% 1.03-3.21 p: 0.039) and day 3 3 .54 (95% CI 1.36-9.26 p: 0.001). Lactate was also an independent predictor of mortality with HR of 1.9 (95% CI 1.08-3.35 p: 0.026) In the estimate of clinical severity given by the presence of septic shock, the MPV on day 3 (8.55fL) and 3 (8.55fL) and the ratios on days 1 (4.42), 2 (4.21) and 3 (6.05), were moderate predictors that reached significance in the ROC curves; like; the established clinical severity SOFA, where the VMP and the VMP / platelet ratio from days 1 to 3 were always higher in non-survivors with significance in all categories Conclusions. The mean platelet volume and the MPV / platelet ratio are predictors of clinical severity and mortality in sepsis. The VMP and the quotient derived from it are indicators that mark the biological behavior of the platelet in sepsis and predict clinical severity and mortality and have a low cost, therefore they should be considered as tools that guide the treatment of sepsis.